2012
DOI: 10.1002/app.36884
|View full text |Cite
|
Sign up to set email alerts
|

Flammability of EVA/IFR (APP/PER/ZB system) and EVA/IFR/synergist (CaCO3, NG, and EG) composites

Abstract: Poly(ethylene-co-vinyl acetate)/intumescent flame retardant (ammonium polyphosphate/pentaerythritol/zinc borate system) composites-EVA/IFR (APP/PER/ ZB system) and EVA/IFR/Synergist [CaCO 3 , natural graphite, or expanded graphite (EG)] composites have been prepared by melting compounding method. The flammability, the combustion process, the quantity of the residual chars, the morphology of the residual chars, and the thermal stability of the chars have been investigated by cone calorimeter, scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 82 publications
2
29
0
Order By: Relevance
“…However, the charred residues of samples (2), (4), and (9) after degradation are kept by 18.8, 12.3, and 10.8 wt% at the high temperature of 700°C, respectively. The possible reason is that EG expands and generates voluminous insulative layers to protect the underlying polymeric matrix when exposed to heat . The result is in agreement with CCT.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, the charred residues of samples (2), (4), and (9) after degradation are kept by 18.8, 12.3, and 10.8 wt% at the high temperature of 700°C, respectively. The possible reason is that EG expands and generates voluminous insulative layers to protect the underlying polymeric matrix when exposed to heat . The result is in agreement with CCT.…”
Section: Resultssupporting
confidence: 82%
“…The charred residues of sample (1) is only 5.1%; however, the charred residues of samples (2), (4), and (9) are about 28.7%, 34.5%, and 38.1% after flammability, respectively. This is attributed to char formation and its morphological structure on the surface of the polymer matrix, and the favorable flame‐retardant synergistic effect of APP + RPM with EG . During the combustion, the compact charred residues may occur on the surface of the burning materials creating a physical protective barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from Table summarize that FPI of HDPE/EVA was 0.0044; however, FPI of HDPE/EVA/EG1 and HDPE/EVA/EG2 increased to 0.6371 and 0.4435, which were about 145 and 101 times of that of HDPE/EVA, respectively. Generally, the higher FPI and lower PHRR, the better is the fire resistance to reduce the loss and casualty in a real fire . This indicated that the flame‐retardant properties of HDPE/EVA/EG were improved greatly by the addition of EG.…”
Section: Resultsmentioning
confidence: 98%
“…Fire performance index (FPI), the ratio of TTI and PHRR, is generally used to design the escape time for firefighters in a real fire . The data from Table summarize that FPI of HDPE/EVA was 0.0044; however, FPI of HDPE/EVA/EG1 and HDPE/EVA/EG2 increased to 0.6371 and 0.4435, which were about 145 and 101 times of that of HDPE/EVA, respectively.…”
Section: Resultsmentioning
confidence: 99%